Classroom management problems in large classes and classroom management alternatives in Advanced English I groups at the Foreign Language Department at the University of El Salvador during the term II-2013. - Cornejo Arévalo, Deysi del Carmen; Reyes, Juan Francisco; Mendoza Coreas, José David; Cruz, Juan Carlos (San Salvador, El Salvador : Universidad de El Salvador, 2014)
Nowadays, university language classes are often given in large groups with more than 50 students, even when large classes have been criticized for limiting learning. They make it more difficult for teachers to maintain a good discipline and to monitor students´ work. Large classes are frequently perceived as one of the main barriers to quality learning (UNESCO, 2006). While the definitions of large classes is not well defined, writers such as Murphy (1998), Harmer (2005) and Blatchford (2002) move around the average number of 13 to 17 students for a small class, and more than that for a large one. Classes at the Foreign Language Department at the UES face these problems as well. Teachers from this department have to deal with the heat, noise, misbehavior, and other problematic situations presented in large classes. As an example, the classroom size is not adequate for the large amount of students. According to Hayes (1997), an appropriate classroom has to give the students the opportunity to move freely through activities. Furthermore, the number of desks does not equal the number of students attending the class, and then they have to look for other ones in other classes and it can cause wasting their learning time. Finally, interaction among students and teachers is affected too. Gibbs & Jenkins (1997) reinforced this when saying that large classes also affect one of the most important part of the language learning process such as the interaction and communication between students-teacher and students-students
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Ingles Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2014
Bibliografia : hojas 94-95
texto en Ingles
Keywords: Inglés -- Enseñanza